2021
DOI: 10.3390/ma14081875
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anisotropy in Distinguishing Domination of Néel or Brownian Relaxation Contribution to Magnetic Inductive Heating: Orientations for Biomedical Applications

Abstract: Magnetic inductive heating (MIH) has been a topic of great interest because of its potential applications, especially in biomedicine. In this paper, the parameters characteristic for magnetic inductive heating power including maximum specific loss power (SLPmax), optimal nanoparticle diameter (Dc) and its width (ΔDc) are considered as being dependent on magnetic nanoparticle anisotropy (K). The calculated results suggest 3 different Néel-domination (N), overlapped Néel/Brownian (NB), and Brownian-domination (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In the field of novel cancer therapy, magnetic nanoparticles (MNPs) are widely investigated within magnetic hyperthermia (MH) treatment [1][2][3]. The technique exploits the Néel magnetic relaxation, Brownian rotation, and hysteresis losses of MNPs, when subjected to an alternating magnetic field (AFM), to generate sufficient heat for inducing cancer cell death [4][5][6]. Ferri-or ferromagnetic nanoparticles (F-MNPs) are most desirable for MH applications since their heating capabilities are one order of magnitude greater in comparison with superparamagnetic iron oxide nanoparticles (SPIONs), due to the increase in both their size and dynamic hysteresis area [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of novel cancer therapy, magnetic nanoparticles (MNPs) are widely investigated within magnetic hyperthermia (MH) treatment [1][2][3]. The technique exploits the Néel magnetic relaxation, Brownian rotation, and hysteresis losses of MNPs, when subjected to an alternating magnetic field (AFM), to generate sufficient heat for inducing cancer cell death [4][5][6]. Ferri-or ferromagnetic nanoparticles (F-MNPs) are most desirable for MH applications since their heating capabilities are one order of magnitude greater in comparison with superparamagnetic iron oxide nanoparticles (SPIONs), due to the increase in both their size and dynamic hysteresis area [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[186][187][188][189] The literature also suggests that several factors are dependent on magnetic fluid hyperthermia, such as particle size distribution, magnetic anisotropy, type of MNPs, viscosity, AC magnetic field, etc. [190] The function of anisotropy energy (KV) in distinguishing the domination of Neel/Brownian relaxation was recently investigated in magnetic inductive heating, where three different domination and transitions of 𝜏 eff to 𝜏 b were seen to shift around a threshold anisotropy energy (KV) value. [190] As demonstrated in Figure 9a,b Nguyen et al estimated Specific Loss Power (SLP) for various anisotropy with respect to NPs sizes.…”
Section: Relaxation Mechanismmentioning
confidence: 99%
“…[190] The function of anisotropy energy (KV) in distinguishing the domination of Neel/Brownian relaxation was recently investigated in magnetic inductive heating, where three different domination and transitions of 𝜏 eff to 𝜏 b were seen to shift around a threshold anisotropy energy (KV) value. [190] As demonstrated in Figure 9a,b Nguyen et al estimated Specific Loss Power (SLP) for various anisotropy with respect to NPs sizes. The effective role of the NPs diameter in determining the Neel or Brownian contributions was established using the Linear Response Theory for smaller NPs.…”
Section: Relaxation Mechanismmentioning
confidence: 99%
“…They also proposed that, in a fluid system, the magnetization in the Néel regime was predominantly affected by the magnetic dipole interactions of MNPs, which reduced K , in contrast to the relatively unaffected magnetization in the Brownian regime. Nguyen et al [ 41 ] showed that the transition from the Néel to the Brownian regime did not occur in a continuous way, but abruptly changed around the critical anisotropy constant ( K C ), which depended on the AMF frequency and the viscosity of the ferrofluid as: where, A = 214.63 kJ·m −3 , B = 81.4 ns, and f 0 = 81.27 kHz are fitting constants.…”
Section: Theoretical Foundations Of Magneto-mechanical Mnp-assisted P...mentioning
confidence: 99%